2017
DOI: 10.1007/s12149-017-1206-z
|View full text |Cite
|
Sign up to set email alerts
|

The effect of short-term treatment with lithium carbonate on the outcome of radioiodine therapy in patients with long-lasting Graves’ hyperthyroidism

Abstract: The short-term treatment with LiCO as an adjunct to I improves efficacy of RIT in patients with long-lasting GH. A success of RIT achieves faster in lithium-treated than in RI group. Treatment with LiCO for 7 days prevents transient worsening of hyperthyroidism after RIT. Short-term use of LiCO shows no toxic side effects.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
10
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(11 citation statements)
references
References 29 publications
1
10
0
Order By: Relevance
“…Our patient’s daily dose of 900 mg was on the higher end of the doses studied in the literature so far. Studies have also suggested that a short course of Li (around 7 days) after administration of RAI dose is most beneficial for RAI [ 16 , 17 ]. The immediate improvement in thyroid function testing in our patient with the combination of Li and SSKI confirms that Li has an additive effect with SSKI.…”
Section: Discussionmentioning
confidence: 99%
“…Our patient’s daily dose of 900 mg was on the higher end of the doses studied in the literature so far. Studies have also suggested that a short course of Li (around 7 days) after administration of RAI dose is most beneficial for RAI [ 16 , 17 ]. The immediate improvement in thyroid function testing in our patient with the combination of Li and SSKI confirms that Li has an additive effect with SSKI.…”
Section: Discussionmentioning
confidence: 99%
“…Pre-treatment is also necessary in the above scenarios. These preparations before RIT include administration of ATDs (e.g., methimazole and propylthiouracil), lithium carbonate, or prednisone [13][14][15][16][17][18][19][20]. Lugol's solution can be used in these circumstances as well as to prevent hyperthyroidism crisis.…”
Section: Discussionmentioning
confidence: 99%
“…Thus the goal of attaining hypothyroidism by RAIT in patients with GD and STN (21) was successful in this series with the rest remained euthyroid, indicating favorable treatment outcome which in turn indicates the appropriate standard of institutional practice. The finding of GD requiring RAIT for up to four instancesmay be taken as a call to consider lithium therapy in long standing GD (22).…”
Section: Discussionmentioning
confidence: 99%